Production and Trade Scenario of Major Underutilized Crops of Nepal - Damodar Gautam; Bhuwan Subedi (Journal of Applied Agricultural Science and Technology, 2022)
In Nepal, underutilized crops are the crop species which have high potential for food, nutrition, dietary and culinary diversification but are less prioritized in formal research, education, extension and development. Analysis of the trend of production and trade helps to formulate and prioritize governing policies for the development of the underutilized crops in Nepal. Analyzing this need, This study aims to reveal the production and trade scenario of major underutilized crops of Nepal; mainly Finger millet, Buckwheat and Barley over the years. Secondary data collected from Food and Agriculture Organization Corporate Statistical Database (FAOSTAT), Ministry of Agriculture and Livestock Development (MoALD), Department of Customs and relevant articles were used for the study and to analyze the ongoing trend, simple linear regression model was used. Collected and analyzed data revealed that, production area of millet is decreasing. However, the production quantity is increasing mainly because of the increased productivity. Though the production is increasing, the import of millet is also high. Increased consumption of local liquor products made from millet followed by diversified food product consumption have seems to conduced the increased demand. The production area of buckwheat found steady over a decade, however, the production and productivity is increasing. The production area and productivity of barley is decreasing while the import of barley is increasing from 2013/14 with the sudden fall in 2019/20. The sudden decrease in import in 2019/20 was due to trade restriction due to Covid situation. But now the demand of these underutilized crops is increasing year after year, and this will continue in forthcoming years also, mainly because of raise in awareness about the health and nutritional benefits. To reduce the ballooning trade deficit of these crops in near future, along with productivity, effective area expansion policies and programs should be formulated and implemented from all three tiers of government.